Place-based sustainability—act or wait-and-see? - Zemite, Ieva; Kunda, Ilona (Frontiers in Political Science, 2023)
There has been a "territorial turn" in exploring sustainable development in the past two decades. Sustainability is increasingly seen as rooted in local resources, relationships, and values. Cultural and creative industries (CCIs) are a substantial local resource and participants of local development.One of the most important relationships of CCIs is with local municipalities, which usually have an overview of local resources, and a role of redefining national level policy ideas, including those pertaining to cultural and art activities. The paper examines place-based development in Valmiera County as a case of national cultural policy translation, grounded in interpretations of the availability of local resources for change.The paper argues that the trajectories of local cultural development are indeed strongly related to local development agents' interpretations of available local resources, including active CCIs. In negotiating the preferred development paths, the stakeholders tend to respond to one of two strategies carried out by the local municipality: Act (taking upon themselves the role of a cultural operator) or Wait-and-see (enabling other cultural operators, the private and non-governmental CCI sector). The paper also highlights the role of creative intermediaries in negotiation processes. The Wait-and-see approach is seen as preferable and more sustainable in the long run.